RNA helicase MOV10 suppresses fear memory and dendritic arborization and regulates microtubule dynamics in hippocampal neurons - Temirlan Shilikbay; Aatiqa Nawaz; Megan Doon; Stephanie Ceman (BMC Biology)
Abstract Background RNA helicase MOV10 is highly expressed in postnatal brain and associates with FMRP and AGO2, suggesting a role in translation regulation in learning and memory. Results We generated a brain-specific knockout mouse (Mov10 Deletion) with greatly reduced MOV10 expression in cortex and hippocampus. Behavior testing revealed enhanced fear memory, similar to that observed in a mouse with reduced brain microRNA production, supporting MOV10’s reported role as an AGO2 cofactor. Cultured hippocampal neurons have elongated distal dendrites, a reported feature of augmin/HAUS over-expression in Drosophila da sensory neurons. In mitotic spindle formation, HAUS is antagonized by the microtubule bundling protein NUMA1. Numa1 mRNA is a MOV10 CLIP target and is among the genes significantly decreased in Mov10 Deletion hippocampus. Restoration of NUMA1 expression and knockdown of HAUS rescued phenotypes of the Mov10 Deletion hippocampal neurons. Conclusions This is the first evidence of translation regulation of NUMA1 by MOV10 as a control point in dendritogenesis.